Rubberband Effect in Temporal Control of Mismatch Negativity - Wang, Lingyan; Lin, Xiaoxiong; Zhou, Bin; Pöppel, Ernst; Bao, Yan (Frontiers in Psychology, 2016)
Mismatch negativity (MMN) is a difference ERP wave reflecting the brain’s automatic reaction to deviant sensory stimuli, and it has been proven to be a useful tool in research on cognitive functions or clinical disorders. In most MMN studies, amplitude, peak latency, or the integral of the responses, in rare cases the slopes of the responses, have been employed as parameters of the ERP responses for quantitative analyses. However, little is known about correlations between these parameters. To better understand the relations between different ERP parameters, we extracted and correlated several different parameters characterizing the MMN waves. We found an unexpected correlation which gives new insight into the temporal control of MMN: response amplitudes are positively correlated with downside slopes, whereas barely correlated with upside slopes. This result suggests an efficient feedback mechanism for the MMN to return to the baseline within a predefined time window, contradicting an exponential decay function as one might expect. As a metaphor we suggest a rubberband effect for the MMN responses, i.e., the larger the distance of the response from neural equilibrium, the stronger the return force to equilibrium.